To what extent do waste management strategies need adaptation to post-COVID-19? - Mahyari, Khadijeh Faraji; Sun, Qiaoyu; Klemeš, Jiří Jaromír; Aghbashlo, Mortaza; Tabatabaei, Meisam; Khoshnevisan, Benyamin; Birkved, Morten (The Science of the total environment, 2022)
The world has been grappling with the crisis of the COVID-19 pandemic for more than a year. Various sectors have been affected by COVID-19 and its consequences. The waste management system is one of the sectors affected by such unpredictable pandemics. The experience of COVID-19 proved that adaptability to such pandemics and the post-pandemic era had become a necessity in waste management systems and this requires an accurate understanding of the challenges that have been arising. The accurate information and data from most countries severely affected by the pandemic are not still available to identify the key challenges during and post-COVID-19. The documented evidence from literature has been collected, and the attempt has been made to summarize the rising challenges and the lessons learned. This review covers all raised challenges concerning the various aspects of the waste management system from generation to final disposal (i.e., generation, storage, collection, transportation, processing, and burial of waste). The necessities and opportunities are recognized for increasing flexibility and adaptability in waste management systems. The four basic pillars are enumerated to adapt the waste management system to the COVID-19 pandemic and post-COVID-19 conditions. Striving to support and implement a circular economy is one of its basic strategies.
Keywords: odpadky - odstraňování; pandemie; nakládání s odpady; COVID-19; Pandemics; Solid Waste; Pandemic; Humans; Waste Management; Waste management hierarchy; Waste management; lidé; Refuse Disposal; Municipal solid waste; Medical waste; tuhý odpad